Breaking Systematic Corruption Through a Strategic Intelligence-Based Job Rotation Policy (A Study on Cross-Institutional Government Agencies at the Central Government Level in Indonesia) - Popy Rufaidah; I Gusti Ngurah Bagus Sucitra; Edy Supriyadi (Eduvest - Journal of Universal Studies, 2026)
Corruption remains a critical challenge in public governance, particularly in Indonesia, where it undermines economic development, institutional integrity, and public trust. This study aims to examine the role of job rotation policies, transparency, and strategic intelligence in reducing corruption within central government institutions. A qualitative research approach was employed, involving in-depth interviews with nine high-level civil servants from ministries and non-ministerial agencies. Data were collected through interviews, documentation, and literature review, and analyzed using Creswell’s qualitative analysis model supported by intelligence analysis techniques. The findings reveal that corruption is driven by factors such as political pressure, weak supervision, transactional positions, and a deeply rooted corrupt culture. Job rotation is found to be an effective preventive measure when implemented consistently, transparently, and based on meritocracy, although it cannot function as a standalone solution. Transparency, particularly through e-government systems and open procurement mechanisms, significantly reduces opportunities for corruption and enhances public oversight. Furthermore, strategic intelligence plays a crucial role in identifying risks, profiling officials, and supporting evidence-based decision-making. In conclusion, an integrated approach combining job rotation, transparency, and strategic intelligence is essential to build accountable governance and effectively reduce corruption practices.